Modeling migration dynamics of immigrants: the case of The Netherlands - Govert E. Bijwaard (Institute for the Study of Labor (IZA), 2007)
In this paper we analyze the demographic factors that influence the migration dynamics of recent immigrants to The Netherlands. We show how we can allow for both permanent and temporary migrants. Based on data from Statistics Netherlands we analyze both the departure and the return from abroad for recent non-Dutch immigrants to The Netherlands. Results disclose differences among migrants by migration motive and by country of origin and lend support to our analytical framework. Combining both models, for departure and returning, provides the probability that a specific migrant ends-up in The Netherlands. It also yields a framework for predicting the migration dynamics over the life-cycle. We can conclude that for a complete view of the migration dynamics it is important to allow for both permanent (stayers) migrants and temporary (movers) migrants and that return from abroad should not be neglected.
Keywords: 330; Rückwanderung; Einwanderung; Migranten; Lebenszyklus; Niederlande